Six years of adaptive and on-farm spring cereal research in Newfoundland - Spaner, D.; McKenzie, D. B.; Todd, A. G.; Simms, A.; MacPherson, M.; Woodrow, E. F. (Canadian Journal of Plant Science, 2000)
Livestock farmers in Newfoundland use most available land for forages. The local production of feed grains is negligible and expensive imported feed accounts for almost one half of farm operating expenses. Here, our objectives were to develop basic agronomic principles of mechanized spring grain production and to demonstrate grain production techniques to the Newfoundland farming community. Barley seeding date trials were conducted at five environments in eastern and western Newfoundland between 1996 and 1998. The relationship between soil pH and barley grain yield was explored through grid soil and yield sampling in two large fields in both 1997 and 1998. Between 1993 and 1998 over 20 livestock farmers throughout Newfoundland cooperated with the Newfoundland Grain Project, growing and comparing varieties of barley (Hordeum vulgare L.), spring wheat (Triticum aestivum L.) and oats (Avena sativa L.) on their farms. Late seeding of barley in the spring/summer resulted in linear grain yield reductions. A levelling off of yield response did not occur at greater cumulated growing degree days, possibly because optimum accumulation for maximum barley yield potential does not occur in Newfoundland. Resistant regression lines, describing the relationship between soil pH and grain yield were developed for two barley varieties, indicated that Sterling reached a yield plateau around a soil pH 6 in 1998, while Chapais reached a yield plateau at soil pH 5.4 in 1997. Barley is well adapted to Newfoundland growing conditions, normally providing a high-yielding, mature grain of good feeding quality. Farmers collaborating with the project were generally impressed with the potential of growing barley for grain and some are now regularly doing so. Key words: Seeding date; barley; wheat; oats; precision farming research